Nature red in tooth and claw theism and the problem of animal suffering - Murray, Michael J. (Oxford : Oxford University Press, 2008)
Those who believe in God often puzzle over how God could permit evil and suffering in the world. 'Nature Red in Tooth and Claw' focuses specifically on non-human animal suffering, and whether or not it raises problems for belief in the existence of a perfectly good creator.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Good and evil; Theism; Animal welfare